Customer spending intenton after withdrawal of full amount of contribution at age 55 years old from Employee Provident Fund (EPF), in Ipoh Perak / Masdzura Shaaidin - Shaaidin, Masdzura (Faculty of Business and Management, 2005)
Employee Provident Fund (EPF) is a security society that was established on October 1951 follows an act 1991. This an act to amend and re-enact the law relating to provident fund for persons employed in certain occupations and for the matter incidental thereto, be it enacted by Seri Paduka Baginda Yang Di-pertuan Agong wit the advice and consent of the Dewan Negara and Dewan Rakyat in Parliament assembled, and by authority of the same, as follow-This Act may be cited as the Employee Provident Fund Act 1991 and this act shall come into force on such as date as the minister may, by notification in the Gazette ,appoint. In the early years, the EPF offered only four types of withdrawal schemes, namely the Age 55 Withdrawal Scheme, Death Withdrawal scheme, the Incapacitation Withdrawal Scheme and Leaving the Country Withdrawal Scheme. Its growth as a retirement saving scheme for the last 54 years has proven that the EPF has stood by its original objective, which is to provide retirement saving for all employees in Malaysia. For the purpose of this study, the descriptive research will be deployed. Primary data will be obtained from a survey by interviewing using questionnaires to 50 respondents. Most of the secondary data was taken from EPF annual report, previous research report related books, magazines and also journal. All the data collected from respondent were transferred into data sheet by using computer software know as SPSS.